Analysis Of The Density Of Coliform Bacteria As An Indicator Of Pollutant In The River Aek Katia Labuhan Batu District - Ika Rosenta Purba; Arman Harahap; Bitondo Dieudonne (International Journal of Science and Environment (IJSE), 2022)
Coliform bacteria is a one of a kind negative bacteria commonly found in the river aek katia in kabupaten labuhanbatu, the presence of coliform bacteria can be an indicator of biology that is important to know the environmental conditions. This study aims to determine the environmental conditions based on biological indicators in the form of an abundance of coliform bacteria in the river Aek Katia Kabupaten Labuhanbatu. The main ingredient in this study is the river water and sediment. The results obtained are still below the quality standard so that the river aek katia in good condition biologically. The presence of coliform bacteria in the river can affect human and biota. So it needs to be considered in the efforts of the management of the environment of the community , especially in an effort to maintain the sustainability of fisheries resources.